Counseling on fighting germs with a healthy lifestylefor children at a course institution - Riri Safitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Health education initiated at an early age is crucial for raising children's awareness about maintaining their personal health and their environment. Consequently, the author conducted a community service activity in the form of a health education session titled